Quantitative analysis and future expectations of the road network in Rashidiya district - Khalid Hassan Aziz , Maryam; Sabah Alwan Al-Khafaji, Samah (Journal of College of Education, 2022)
Abstract The study showed a quantitative analysis of the road network in Rashidiya district according to the (density) criterion for the population and area variables, and the actually cultivated area, which ended with a variation according to the population numbers, the area of each district and the lengths of the roads in it, and the actually cultivated area is disproportionate to the lengths of the roads because the cultivated area It is actually less than (100) dunams, and this measure was used (average population served by roads) and (average area served by roads), as the result of (average population served by roads) was high in the province of (the southern bid’ah) because it includes urban centers compared to other provinces that dominate It is the rural environment, while (the average area served by roads) was few in the study area as it occupies large agricultural areas and other uses compared to the area allocated for transportation, while the measure (per person’s share of roads) was low in most of the provinces of the study area with the exception of the province (Northern Bid’ah) Because of the small number of the population, offset by the longest roads that cover their needs, the researcher sought to know the (vehicle traffic density) on the main and secondary roads of the study area through the field study. It has three peaks: (7-10) in the morning, (12-3) in the afternoon, and (4-7) in the evening, which ended with the varying traffic intensity from one road to another according to its vital importance and the areas it serves. Finally, the study came with a future prediction of population size, area, and road lengths for the purpose of developing appropriate solutions to accommodate this growth and reduce transportation problems. While this density varied on secondary roads, the traffic density on the secondary road (Al Rashidiya Tourist South) is (1,336) vehicles / day, different from the traffic density on the secondary road (the storm) (54) vehicles / day due to human factors, and the study revealed future expectations For Rashidiya roads according to the variables (population numbers, area, lengths of roads), it was shown that the lengths of the roads will remain the same (106) km, compared to a high population (83,969) people and a small area (99) km 2, which requires taking the necessary measures by the authorities concerned in this regard, to accommodate population and urban growth.